Modeling Nodes and Cells of Neuron-Equivalentors as Accelerators of Equivalental-Convolutional Self-Learning Neural Structures - Krasilenko, Vladimir; Nikitovych, Diana; Lazarev, Alexander (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
In the paper, we consider the urgent need to create highly efficient hardware accelerators for machine learning and deep convolutional neural networks (CNNs), for associative memory models, clustering, and pattern recognition. We show a brief overview of our related works the advantages of the equivalent models (EM) for describing and designing bio-inspired systems. The capacity of neural net on the basis of EM and of its modifications is in several times quantity of neurons. Such neuro-paradigms are very perspective for processing, clustering, recognition, storing large size, strongly correlated, highly noised images and creating of uncontrolled learning machine. And since the basic operational functional nodes of EM are such vector-matrix or matrix-tensor procedures with continuous-logical operations as: normalized vector operations "equivalence", "nonequivalence", and etc., we consider in this paper new conceptual approaches to the design of full-scale arrays of such neuron-equivalentors (NEs) with extended functionality, including different activation functions. Our approach is based on the use of analog and mixed (with special coding) methods for implementing the required operations, building NEs (with number of synapsis from 8 up to 128 and more) and their base cells, nodes based on photosensitive elements and CMOS current mirrors. Simulation results show that the efficiency of NEs relative to the energy intensity is estimated at a value of not less than 1012 an. op. / sec on W and can be increased. The results confirm the correctness of the concept and the possibility of creating NEs and MIMO structures on their basis. У статті ми розглядаємо нагальну потребу у створенні високоефективних апаратних прискорювачів для машинного навчання та глибоких згорткових нейронних мереж (CNN), для асоціативних моделей пам’яті, кластеризації та розпізнавання образів. Ми показуємо короткий огляд наших пов’язаних робіт із перевагами еквівалентних моделей (ЕМ) для опису та проектування систем, натхненних біотехнологіями. Ємність нейронної мережі на основі ЕМ та її модифікацій у декілька разів перевищує кількість нейронів. Такі нейропарадигми дуже перспективні для обробки, кластеризації, розпізнавання, зберігання великого розміру, сильно корельованих, сильно зашумлених зображень і створення некерованої самонавчальної машини. А оскільки основними операційними функціональними вузлами ЕМ є такі векторно-матричні або матрично-тензорні процедури з неперервно-логічними операціями, як: нормалізовані векторні операції «еквівалентність», «нееквівалентність» та ін., то в цій роботі розглядаються нові концептуальні підходи до проектування повномасштабних масивів таких нейронів-еквівалентів (НЕ) з розширеною функціональністю, включаючи різні функції активації. Наш підхід заснований на використанні аналогових і змішаних (зі спеціальним кодуванням) методів для реалізації необхідних операцій, побудови НЕ (з кількістю синапсів від 8 до 128 і більше) і їх базових комірок, вузлів на основі фоточутливих елементів і КМОП. поточні дзеркала. Результати моделювання показують, що ефективність НЕ відносно енергоємності оцінюється на рівні не менше 10^12 а. ор. / сек на Вт і може бути збільшена. Результати підтверджують правильність концепції та можливість створення на їх основі NE та структур MIMO.